Potential implications of blood flow restriction exercise on vascular health: A brief review - da Cunha Nascimento, D.; Schoenfeld, B. J.; Prestes, J. (Sports Medicine, 2020)
Blood flow restriction (BFR) exercise (a.k.a. occlusion training) has emerged as a viable surrogate to traditional heavy-load strength rehabilitation training for a broad range of clinical populations including elderly subjects and rehabilitating athletes. A particular benefit of BFR exercise is the lower stress upon the joints as compared to traditional heavy resistance training, with similar gains in muscle strength and size. The application of an inflatable cuff to the proximal portion of the limbs increases the pressure required for venous return, leading to changes in venous compliance and wall tension. However, it is not known if long-term benefits of BFR exercise on muscle strength and size outweigh potential short and long-term complications on vascular health. BFR exercise could lead to clinical deterioration of the vasculature along with sympathetic overactivity and decreased vascular function associated with retrograde shear stress. This raises a fundamental question: Given the concern that excessive restriction could cause injury to endothelial cells and might cause detrimental effects on endothelial function, even in healthy individuals, should we critically re-evaluate the safety of this method for the general population? From this perspective, the purpose of this manuscript is to review the effects of BFR exercise on vascular function, and to provide relevant insights for training practice as well as future directions for research. Key points Many studies have investigated the role of blood flow restriction exercise on muscle size and strength; however, these studies were not designed to answer the question as to whether this method may impose short- or long-term complications on vascular health. The evidence suggests that practitioners must be cognizant of the fact that BFR training may have deleterious effects on endothelial cells, particularly if proper precautions are not followed. Setting the restriction pressure calculated as a percentage of each subject`s arterial occlusion pressure (i.e., 40-60%) appears to be the only method for creating a similar blood flow restriction without reaching full arterial occlusion due to high pressures; this might help to avoid the deleterious effects during daily practice.